For the Metaphysical Foundations of Leadership Ethics - Lekka-Kowalik, Agnieszka (Roczniki Filozoficzne, 2025)
The paper analyzes some aspects of leadership ethics as proposed by Jarosław Kucharski. Starting with the evaluative term ‘leader’, the article shows that (1) the leader’s responsibility must be extended to include the responsibility for entities that are affected by the consequences of his or her actions; (2) the human being as a person is the measure the leader’s actions that are to change the state of affairs “for the better”; (3) the same criterion should be applied when assessing the axiological integrity of the leader. Kucharski rightly demands some metaphysical foundations for the ethics of leadership. However, when they are indicated – as the concept of human beings and their good – the distinction he proposes between the “star-shaped” and “parallel” models of integrity turns out to be a cognitive misunderstanding.